Myeloid-Derived Suppressor Cells Promote the Progression of Primary Membranous Nephropathy by Enhancing Th17 Response - Li, Huimin; Wu, Hao; Guo, Qiaoyan; Yu, Hongyu; Xu, Ying; Yu, Jinyu; Wang, Zhongkun; Yi, Huanfa (Frontiers in Immunology, 2020)
Many studies have confirmed that myeloid-derived suppressor cells (MDSCs) are closely related to autoimmune diseases, but their exact role in these processes remains largely unclear. Here, we investigate this question in patients with primary membranous nephropathy (PMN). Compared to healthy controls (HCs), PMN patients showed a significantly increased number of HLA-DR−CD11b+CD33+ MDSCs in the peripheral blood, including both CD14+CD66b− monocytic and CD14−CD66b+ granulocytic MDSCs. The frequency of MDSCs was positively correlated with the levels of serum anti-phospholipase A2 receptor (anti-PLA2R) levels, 24-hour urine protein quantification, and disease activity in PMN patients. Consistently, enhanced T helper 2 (Th2) and T helper 17 (Th17) immune responses were positively associated with plasma anti-PLA2R levels, 24-hour urine protein quantification, and the disease activity of PMN patients. Moreover, in comparison with HCs, MDSCs from PMN patients exhibited significantly elevated arginase-1 (ARG-1) production and increased the potential to promote Th17 differentiation in vitro in an ARG-1–dependent manner. This study directly demonstrated a pathogenic role for MDSCs in human PMN and provides a molecular mechanism for the pathogenesis of PMN. Our data show that MDSCs may promote PMN disease progression mainly by enhancing Th17 response, and MDSCs may be an important indicator for diagnosis and for monitoring both the therapy and prognosis of PMN diseases.